Human Induced Pluripotent Stem Cell‐Derived Neural Progenitor Cells Produce Distinct Neural 3D In Vitro Models Depending on Alginate/Gellan Gum/Laminin Hydrogel Blend Properties. Issue 16 (1st July 2021) - Kapr, Julia; Petersilie, Laura; Distler, Thomas; Lauria, Ines; Bendt, Farina; Sauter, Clemens M.; Boccaccini, Aldo R.; Rose, Christine R.; Fritsche, Ellen
Abstract: Stable and predictive neural cell culture models are a necessary premise for many research fields. However, conventional 2D models lack 3D cell‐material/‐cell interactions and hence do not reflect the complexity of the in vivo situation properly. Here two alginate/gellan gum/laminin (ALG/GG/LAM) hydrogel blends are presented for the fabrication of human induced pluripotent stem cell (hiPSC)‐based 3D neural models. For hydrogel embedding, hiPSC‐derived neural progenitor cells (hiNPCs) are used either directly or after 3D neural pre‐differentiation. It is shown that stiffness and stress relaxation of the gel blends, as well as the cell differentiation strategy influence 3D model development. The embedded hiNPCs differentiate into neurons and astrocytes within the gel blends and display spontaneous intracellular calcium signals. Two fit‐for‐purpose models valuable for i) applications requiring a high degree of complexity, but less throughput, such as disease modeling and long‐term exposure studies and ii) higher throughput applications, such as acute exposures or substance screenings are proposed. Due to their wide range of applications, adjustability, and printing capabilities, the ALG/GG/LAM based 3D neural models are of great potential for 3D neural modeling in the future. Abstract : The manuscript describes two fit‐for‐purpose approaches to generate 3D in vitro neural models based on human induced pluripotent stem cells. It is shown that stiffness and stress relaxation of the proposed gel blends, as well as the cell differentiation strategy influence the 3D model development. Successful differentiation and intracellular calcium signaling within the 3D microtissues are further shown.